D’étudiant à chercheur - Alain Baudrit (Éducation et Socialisation)
For students, becoming full-fledged researchers is not easy given the methodological and scientific requirements. During investigation activities of an iterative nature, they can be helped in this by teachers but also benefit from the contribution of digital tools, hence the notions of teaching presence and digital presence examined in this article in support of work carried out on these questions. It is through interviews, testimonies, questionnaires or analysis of research journals written by students that these points are studied within the framework of research training in higher education. The two types of presence show distinct effects in terms of skills in carrying out investigations and present some limits in terms of autonomy acquired by students to develop their own researches. Concerning this last point, the exercise of critical thinking presents itself as a path to be taken seriously through a diversity of methods, tools and educational supports.